Analyzing the coexistence of conflict and cooperation in a regional delta management system: Tidal River Management (TRM) in the Bangladesh delta. (5th July 2019) - Mutahara, Mahmuda; Warner, Jeroen; Khan, M. Shah Alam
Abstract: This article analyzes the history and dynamics of conflict and cooperation in a local and regional delta management system focusing on tidal river management (TRM). TRM was formally implemented through a participatory approach since early 2000 to address waterlogging problems in the southwest delta of Bangladesh. There have been, and still are, serious difficulties in achieving the full potential of TRM because multistakeholder processes (MSPs) are not effectively sustained. One major cause of ineffective MSPs is incompetent dealing with conflict and cooperation among stakeholders. Our research was a participatory assessment of water management events focusing on the causes, intensity, and trend of conflict and cooperation in TRM practices over the last 30 years. The results show that the history of TRM appeared more conflictive than cooperative, and also the cooperations between major stakeholders were rarely sustained in TRM practices. To that effect, we applied an adapted "Transboundary Water Interaction Nexus (TWINs)" model to this local water management context, which explores the interrelatedness of conflict and cooperation for learning to deal with MSPs in local delta water management. The research findings should be helpful for improving participation policy in water management in Bangladesh and also facilitate MSPs in delta water governance elsewhere.